Importance of allergen–environment interactions in epidemic thunderstorm asthma. (May 2022) - Hughes, Kira Morgan; Price, Dwan; Suphioglu, Cenk
Australia is home to one of the highest rates of allergic rhinitis worldwide. Commonly known as 'hay fever', this chronic condition affects up to 30% of the population and is characterised by sensitisation to pollen and fungal spores. Exposure to these aeroallergens has been strongly associated with causing allergic reactions and worsening asthma symptoms. Over the last few decades, incidences of respiratory admissions have risen due to the increased atmospheric concentration of airborne allergens. The fragmentation and dispersion of these allergens is aided by environmental factors like rainfall, temperature and interactions with atmospheric aerosols. Extreme weather parameters, which continue to become more frequent due to the impacts of climate change, have greatly fluctuated allergen concentrations and led to epidemic thunderstorm asthma (ETSA) events that have left hundreds, if not thousands, struggling to breathe. While a link exists between airborne allergens, weather and respiratory admissions, the underlying factors that influence these epidemics remain unknown. It is important we understand the potential threat these events pose on our susceptible populations and ensure our health infrastructure is prepared for the next epidemic.